2008
DOI: 10.1179/174328407x240954
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion simulations of MC and M7C3 carbide coarsening in bcc and fcc matrix utilising new thermodynamic and kinetic description

Abstract: A new thermodynamic database has been combined with an existing kinetic database to perform coarsening simulations in ternary systems including MC and M7C3 carbides in an fcc matrix. The kinetic database was revised taking into consideration the new experimental information on the Fe–Cr–V–C system obtained in the present work, and available experiments on the ternary Fe–Cr–C and Fe–V–C systems. After revision the agreement between experimental results and simulations was satisfactory. It was found that the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 31 publications
1
7
0
1
Order By: Relevance
“…Mobility of Cr MQ(bcc,Cr:Va;0) À407000 [3] MF(bcc,Cr:Va;0) À35.6AET MQ(bcc,Fe:Va;0) À218000 [3] MF(bcc,Fe:Va;0) À77.93AET MQ(bcc,V:Va;0) À270500 [29] MF(bcc,V:Va;0) À115.26AET Mobility of V MQ(bcc,Cr:Va;0) À418826 [30] MF(bcc,Cr:Va;0) À27.246AET MQ(bcc,Cr,Fe:Va;0) 262769 [31,32] MF(bcc,Cr;Fe:Va;0) À117.559AET The investigations included SEM backscattered electron analysis which gave micrographs for image analysis, EBSD studies in FEG SEM to verify the carbide and matrix phase structure, and EDS/WDS measurements to obtain the composition of the carbides as well as that of the matrix.…”
Section: Methodsmentioning
confidence: 99%
“…Mobility of Cr MQ(bcc,Cr:Va;0) À407000 [3] MF(bcc,Cr:Va;0) À35.6AET MQ(bcc,Fe:Va;0) À218000 [3] MF(bcc,Fe:Va;0) À77.93AET MQ(bcc,V:Va;0) À270500 [29] MF(bcc,V:Va;0) À115.26AET Mobility of V MQ(bcc,Cr:Va;0) À418826 [30] MF(bcc,Cr:Va;0) À27.246AET MQ(bcc,Cr,Fe:Va;0) 262769 [31,32] MF(bcc,Cr;Fe:Va;0) À117.559AET The investigations included SEM backscattered electron analysis which gave micrographs for image analysis, EBSD studies in FEG SEM to verify the carbide and matrix phase structure, and EDS/WDS measurements to obtain the composition of the carbides as well as that of the matrix.…”
Section: Methodsmentioning
confidence: 99%
“…Comparisons of experimentally measured precipitate coarsening rates with simulated rates have also been used to validate mobility parameters. [4,5] In the current work the assessed parameters were validated by comparing calculated ternary diffusion coefficients with experimentally measured coefficients and by comparing a calculated coarsening rate of a Mo rich M 6 C carbide with its measured coarsening rate. For the latter comparison a coarsening experiment was performed.…”
Section: Diffusion Mobility Modellingmentioning
confidence: 99%
“…However, some reported assessments exist; Jönsson [3] performed assessments for the diffusion of several elements in both the fcc and the bcc phases with focus on iron based systems, Bratberg et al [4] revised the kinetic description of Cr and V diffusion in the fcc phase and Lindwall and Frisk [5] assessed parameters for the diffusion in the bcc V-Cr-Fe system. The latter work focused on the V diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…26) Some researchers gave the kinetics description of secondary carbides and discussed when the precipitation will occur. 2,27,28) Almost all of the literature reports concluded that precipitation occurred during the holding period, as is shown in Table 1.…”
Section: Secondary Carbides Formationmentioning
confidence: 99%